Temporary Super Depreciation Allowances for Green and Digital Investments - Michael Funke; Raphael Terasa (Center for Economic Studies and ifo Institute (CESifo), 2022)
As an incentive to increase high-impact investment and boost growth, the German Federal Government is planning to introduce a targeted temporary super depreciation allowance to support much-needed green and digital transitions. Using a calibrated multi-sector DSGE model, we find that the temporary super deduction could trigger an uplift of 10 percentage points for green and digital capital spending, turbo-charging green growth ambitions. However, with the temporary measure set to end after two years, there is a risk that business investment could tail off at a crucial time, when post-COVID-19 recovery is levelling out. Thus, additional longer-term climate policies are needed to drive the green transition, facilitated by broad policy packages.
Keywords: E22; E60; H25; Q54; Q58; 330; climate economics; business taxation; firm investment; depreciation allowances; DSGE model; Germany